Amelioration of Salinity Stressed Soil Using Natural Zeolite for Improving Soil Properties and Chinese Cabbage Agronomic Performances - Romadhan, Tantrie D; Marwanto, Marwanto; Murcitro, Bambang G; Handajaningsih, Merakati (Akta Agrosia, 2022)
Salinity stress is the major abiotic stress for crop production. The purpose of this study was to evaluate the effectiveness of zeolite on improving soil properties, the growth, and yield of Chinese cabbage. This pot experiment was conducted from September to November 2020 at the Research and Teaching Field of the Faculty of Agriculture, consisted of 6 treatment levels, i.e. (1) control, (2) soil + 6.9 g NaCl /10 kg soil, (3) soil + 6.9 g Na2SO4 /10 kg soil, (4) soil + 3.2 g zeolite /10 kg soil, (5) soil + 6.9 g NaCl /10 kg soil + 3.2 g zeolite /10 kg soil, and (6) soil + 6.9 g Na2SO4 /10 kg soil + 3.2 g zeolite /10 kg of soil, and arranged in a completely randomized design with 3 replications. The application of zeolite decreased the EC of salinized soil and increased the soil CEC. NaCl salinity stress reduced plant height (23%), number of leaves (22%), fresh weight of roots (165%), dry weight of roots (170%), stalk length (32%), and plant dry weight (131%), while Na2SO4 salinity stress only reduced the number of leaves (23%). The addition of zeolite to salinized NaCl soil increased stalk length (39%), plant fresh weight (172%), leaf fresh weight (174%), plant dry weight (133%), and leaf dry weight (23%), while to salinized Na2SO4 soil only increased plant dry weight (90%) and leaf dry weight (177%). The overall results show that the addition of zeolite can effectively ameliorate salinity stress due to NaCl.